2007
DOI: 10.1158/1078-0432.ccr-06-2945
|View full text |Cite
|
Sign up to set email alerts
|

A New Diagnostic Marker for Secreted Epstein-Barr Virus–Encoded LMP1 and BARF1 Oncoproteins in the Serum and Saliva of Patients with Nasopharyngeal Carcinoma

Abstract: Purpose: EBV has been associated with nasopharyngeal carcinomas (NPC). In North Africa, the incidence is bimodalöthe first peak occurring at f20 years of age and the second peak occurring at f50 years. Standard diagnostic tests based on immunofluorescence using anti-IgA EBV have shown that young North African patients have a negative serology compared with older patients.We are interested in two EBV-encoded oncoproteins, LMP1and BARF1, which have thus far not been studied in terms of their potential as diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 39 publications
1
83
0
1
Order By: Relevance
“…Importantly, LMP1 was also detected in exosomes purified from the serum of mice carrying the C15 tumor (Fig. 1C, serum), consistent with previous work on NPC patient serum (16).…”
Section: Ebv-infected Npc Produce Exosomes That Activate Growth-signasupporting
confidence: 90%
See 1 more Smart Citation
“…Importantly, LMP1 was also detected in exosomes purified from the serum of mice carrying the C15 tumor (Fig. 1C, serum), consistent with previous work on NPC patient serum (16).…”
Section: Ebv-infected Npc Produce Exosomes That Activate Growth-signasupporting
confidence: 90%
“…Exosomes containing LMP1 have been detected in the serum of NPC patients, and NPC serum has been shown to have mitogenic activity as measured by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay (16). To evaluate the properties of exosomes produced by NPC cells, exosomes were harvested from the media of the NPC C666 cell line, an NPC cell line that has retained EBV but expresses low to undetectable levels of LMP1 (17).…”
Section: Ebv-infected Npc Produce Exosomes That Activate Growth-signamentioning
confidence: 99%
“…LMP1 protein is weakly expressed or undetectable in most of EBV-infected NPC cell lines in normal culture condition in vitro (21,22,34). Interestingly, considerable increase of LMP1 expression has been observed when an EBVpositive NPC cell line is injected into nude mice to develop solid tumors (35). Because ER stress readily occurs under hypoxia or nutrition insufficiency in solid tumors (4), we propose that ER stress/UPR can be a key factor that up-regulates LMP1 in the in vivo condition of NPC tumors.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several lines of evidences suggesting that EBV oncoproteins can be targeted for cancer diagnostics. For instances, Houali and colleagues showed that both EBV oncoproteins, LMP1 and BARF1, could be detected in serum and saliva of NPC patients, and the secreted LMP1 was highly associated with exosome-like vesicles [54]. Both EBV oncoproteins were presented with high mitogenic activity that supported their implication in oncogenic development of NPC.…”
Section: Exosomes As Biomarkersmentioning
confidence: 99%